Role of Social and Self-Regulated Learning in School Contexts - Diana R. Akhmedjanova (Voprosy obrazovaniya / Educational Studies Moscow, 2024)
Self- and socially regulated learning skills allow students to develop soft skills or competencies to tackle learning tasks.  Self-regulated learning skills help students set learning goals, choose learning strategies, monitor their progress, and control their affective and motivational states when working on learning tasks. Socially regulated learning skills help students to use self-regulated learning practices recognizing the reciprocal influence of other people, technology, and environment, creating opportunities for joint regulation of learning. However, it is still not clear how social regulation of learning relates to self-regulated learning. The purpose of this article is to describe the constructs of self- and socially regulated learning, report on the results of recent research studies of their components, introduce a theoretical model of the self- and socially regulated learning, discuss the results of our studies, and identify the areas for future research. The scientific contribution of this article is an attempt to compare the scholarly evidence and theoretical views of Russian and foreign researchers in order to understand the state of research of self- and socially regulated learning in authentic school contexts.